25abc+15bc-5ac=

Simple and best practice solution for 25abc+15bc-5ac= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25abc+15bc-5ac= equation:


Simplifying
25abc + 15bc + -5ac = 0

Reorder the terms:
25abc + -5ac + 15bc = 0

Solving
25abc + -5ac + 15bc = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-15bc' to each side of the equation.
25abc + -5ac + 15bc + -15bc = 0 + -15bc

Combine like terms: 15bc + -15bc = 0
25abc + -5ac + 0 = 0 + -15bc
25abc + -5ac = 0 + -15bc
Remove the zero:
25abc + -5ac = -15bc

Combine like terms: -15bc + 15bc = 0
25abc + -5ac + 15bc = 0

Factor out the Greatest Common Factor (GCF), '5c'.
5c(5ab + -1a + 3b) = 0

Ignore the factor 5.

Subproblem 1

Set the factor 'c' equal to zero and attempt to solve: Simplifying c = 0 Solving c = 0 Move all terms containing a to the left, all other terms to the right. Add '-1c' to each side of the equation. c + -1c = 0 + -1c Remove the zero: 0 = -1c Simplifying 0 = -1c The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(5ab + -1a + 3b)' equal to zero and attempt to solve: Simplifying 5ab + -1a + 3b = 0 Reorder the terms: -1a + 5ab + 3b = 0 Solving -1a + 5ab + 3b = 0 Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. -1a + 5ab + 3b + -3b = 0 + -3b Combine like terms: 3b + -3b = 0 -1a + 5ab + 0 = 0 + -3b -1a + 5ab = 0 + -3b Remove the zero: -1a + 5ab = -3b The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| x/5-7x/10=1/5 | | X/-8=8/9 | | 2x+14=71 | | 0=.125x+12 | | 3x+19y=-7 | | 2(2x+9)=38 | | X-3=13-3x | | X+3x+4(x-1)=-12 | | 0.6x+5.3=4.4 | | 0.6+5.3=4.4 | | -2=3m-5m | | 2cos^2x+sinx=5 | | 3(x-2)=3x+12 | | 2-3x(x-1)= | | 70-(3x+50)=2-5x | | x/17-7x/17=30/17 | | W-10=-25 | | 2+3(x-2)=5x-10 | | 0.7x-7.7(3.6+3.7x)=-241.703 | | X/11=-2/13 | | -4(x+2)=-63 | | 3x+9x-12=180 | | R-11=3 | | -125.994=-6.9(-2.8n-3.3) | | 3(x-6)-4x=20 | | -12+2y=10 | | X+7X^2-63=8 | | 125.994=-6.9(-2.8n-3.3) | | 4x^2+72x+308=0 | | -82.93884=5.8(2.38k-1.9) | | f(x)=-x^2-x+6 | | 2a+4b+8c= |

Equations solver categories